Portrait of Regional Regulations for Public Order and Tranquility in a Tolerant and Inclusive Society in West Sumatra - Deri Rizal; Alfurqan; M. Yemmardotillah; Rahmi Wiza; Edi Saputra; Syuhood B. Kooria (El-Mashlahah, 2025)
The study addressed the gap in understanding how local wisdom and religious moderation are integrated into regional regulations in West Sumatra, a region with rich customary and religious traditions but ranked low on the national tolerance index. Despite having a strong philosophical foundation in Adat Basandi Syara’, Syara’ Basandi Kitabullah, current legal instruments may not adequately reflect these values to foster a tolerant and inclusive society. The study aimed to examine the portrait of regional regulations on public order and public tranquility in West Sumatra from 2009 to 2023, to realize a tolerant and inclusive society. The method used an empirical legal research with a socio-legal approach drawn from primary data in West Sumatra. The findings showed that the Regional Regulations (Perda) in West Sumatra have not yet embodied the principles of public order and social tranquility based on tolerance and inclusivity. Of the 634 Perdas analyzed from 2009 to 2023, only 2.2% addressed issues related to public order. Moreover, they narrowly focused on nuisance permits, alcoholic beverage control, and public morality. Therefore, this indicated a significant gap in incorporating local wisdom and religious values rooted in the Minangkabau philosophy of Adat Basandi Syara', Syara' Basandi Kitabullah, into regulatory frameworks that promote harmony in a pluralistic society.